Foreign Acquisitions in China and Multinationals' Global Market Strategy. Issue 1 (February 2016) - Liu, Qing; Qiu, Larry D.; Li, Zhigang
Abstract: Using firm‐level data from 2000 to 2006, we find that foreign acquisitions in China change the target firms' export extensive margins. We develop a three‐country model with cross‐border acquisitions to show that the acquirers can alter the targets' export decision through three possible channels: fixed‐cost jumping, technology transfer and global market reorganization. We find evidence that foreign acquisitions change the Chinese target firms' probability of exporting to a third market. Technology transfer is not observed. Evidence implies that fixed‐cost jumping is used to enable the targets to export, while global market reorganization is a key motive for the acquirers to withdraw the targets from the export market.